The influence of facial stigma and physical attractiveness on the impressions formation about person - Svetlana V. Zorina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
When a person is perceived, the impression of a person is formed as a result of processing a multitude of signs (features of the face). A significant part of these signals has been studied in sufficient detail, but information on how they interact with each other is not enough. The study is aimed at studying the mechanism of impression formation as a result of the perception of two signals having the opposite effect: physical attractiveness and stigma of disembryogenesis (orbital hypertelorism, manifested in increasing the distance between the inner corners of the eyes). Physical attractiveness enhances a positive impression, while facial stigma contributes to a negative opinion of the person. We expected that the impression will depend on the interaction of the signals with each other. In the experiment, participants (200 people) made judgments about three groups of variables: personality traits, the degree of desired interpersonal proximity, the reliability of a person (danger and potential criminality). To identify the interaction of signals, the division of the photoimage into two parts was used. This technique makes it difficult for the holistic perception of the face, weakening the influence of facial signals. Meaning, changes in the eye area have less impact on the overall impression because the upper and lower halves of the face are perceived separately. The hypothesis was confirmed for social judgments about the reliability of a person. For physically attractive individuals, the violation of continuty contributed to an increase in the attributed likelihood of committing murder and fraud, for physically unattractive a decrease in the perceived danger and the possibility degree of committing fraudulent activities. While perceiving the face of another person, the subject of perception forms a holistic impression in which the initial pieces of information are integrated depending on their weight, for example, a strong signal eliminates a weak one. Obtained results shows that physical attractiveness weakens the influence of dysembryogenesis stigma on the evaluation of potential criminality, forming a positive bias.